2018
DOI: 10.3389/fphar.2018.00329
|View full text |Cite
|
Sign up to set email alerts
|

Trace Amine-Associated Receptor 1 Modulates the Locomotor and Sensitization Effects of Nicotine

Abstract: Trace amine-associated receptor 1 (TAAR1) has emerged as a promising target for addiction treatments because it affects dopamine transmission in the mesolimbic pathway. TAAR1 is involved in the effects of addictive drugs, such as amphetamines, cocaine and ethanol, but the impact of TAAR1 on the effects of nicotine, the psychoactive drug responsible for the development and maintenance of tobacco smoking, has not yet been studied. This study was performed to investigate the possible modulatory action of TAAR1 on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 59 publications
0
10
0
2
Order By: Relevance
“…Although the precise mechanisms of TA 1 in modulating dopamine transmission remain unclear, there is evidence that TA 1 may interact with dopamine D 2 receptors (both presynaptic and postsynaptic) to inhibit dopamine release within the synaptic cleft and the signalling pathways associated with dopamine receptors- (Espinoza et al, 2015;Leo et al, 2014). Consistent with the neurobiological evidence, other results show that activation of TA 1 inhibited the behavioural effects of several drugs of abuse including cocaine (Achat-Mendes, Lynch, Sullivan, Vallender, & Miller, 2012;Pei et al, 2014;Revel, Meyer, et al, 2012;Sukhanov et al, 2018;Thorn et al, 2014). Activation of TA 1 attenuates acute cocaine-induced hyperactivity and chronic cocaine-induced behavioural sensitization (Thorn et al, 2014).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Although the precise mechanisms of TA 1 in modulating dopamine transmission remain unclear, there is evidence that TA 1 may interact with dopamine D 2 receptors (both presynaptic and postsynaptic) to inhibit dopamine release within the synaptic cleft and the signalling pathways associated with dopamine receptors- (Espinoza et al, 2015;Leo et al, 2014). Consistent with the neurobiological evidence, other results show that activation of TA 1 inhibited the behavioural effects of several drugs of abuse including cocaine (Achat-Mendes, Lynch, Sullivan, Vallender, & Miller, 2012;Pei et al, 2014;Revel, Meyer, et al, 2012;Sukhanov et al, 2018;Thorn et al, 2014). Activation of TA 1 attenuates acute cocaine-induced hyperactivity and chronic cocaine-induced behavioural sensitization (Thorn et al, 2014).…”
Section: Discussionmentioning
confidence: 72%
“…Previous studies showed that the TA 1 full agonist RO5166017 and partial agonist RO5203648 attenuated stress‐induced hyperthermia (Revel et al, 2011; Revel, Moreau, et al, 2012), suggesting that TA 1 agonists have anti‐stress properties. The TA 1 full agonists and partial agonists similarly attenuated abuse‐related behaviours of cocaine and nicotine (Liu et al, 2018; Pei et al, 2014; Sukhanov, Dorofeikova, Dolgorukova, Dorotenko, & Gainetdinov, 2018; Thorn et al, 2014). However, there is no study examining the effects of activation of TA 1 by its full and partial agonists, on stress‐induced reinstatement of cocaine‐seeking behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Administration of TAAR1 agonists was able to decrease nicotine-induced hyperactivity (Liu et al, 2018;Sukhanov et al, 2018), sensitization (Liu et al, 2018;Sukhanov et al, 2018), self-administration (Liu et al, 2018), cue-and drugprimed reinstatement (Liu et al, 2018), and discriminative stimulus effects (Liu et al, 2018), while simultaneously increasing the elasticity of the nicotine demand curve (Liu et al, 2018). These beneficial effects of TAAR1 activation were associated with a decrease in the nicotine-induced dopamine release and c-fos expression in the nucleus accumbens, confirming prevention of hyperactivity of the dopamine reward centers (Liu et al, 2018).…”
Section: Ro3648 Ro6390 Ro3397mentioning
confidence: 75%
“…58,59 In fact, previous studies have shown that activation of TAAR1 attenuates cocaine, methamphetamine, morphine and nicotine self-administration, cueand drug-induced reinstatement and ethanol-and nicotine-induced behavioural sensitization. 26,29,30,[60][61][62] Moreover, in our recent study, we showed that TAAR1 agonists were able to reduce the positive reinforcing effects of nicotine by extensive behavioural assay including nicotine self-administration, behavioural sensitization, nicotine discrimination and cue-and drug-induced reinstatement. 30 Furthermore, TAAR1 knockout rats showed higher cue-and drug-induced reinstatement of nicotine-seeking compared with their wide-type littermates.…”
Section: Discussionmentioning
confidence: 95%